Two-Dimensional Fluorescence Difference Spectroscopy to Characterize Nanoparticles and their Interactions - Hurst, Miranda N.; DeLong, Robert K. (My University, 2017)
Two dimensional fluorescence difference spectroscopy (2D FDS) detects nanoparticle interactions following surface functionalization and biomolecule loading by generating a spectral signature of the fluorescent intensity per excitation and emission wavelengths. Comparing metal oxide nanoparticles revealed a unique spectral signature per material composition. 2D FDS showed to be sensitive to changes in surface properties between ZnO NPs synthesized by different methods. ZnO NP loaded with glycol chitosan, polyacrylic acid (PAA), or methoxy polyethylene glycol (mPEG) exhibited a distinct spectral signature shift. ZnO NP loaded with Torula Yeast RNA (TYRNA)(640 nm), polyinosinic: polycytidylic acid (pIC)(680 nm), or splice switching oligonucleotide (SSO)(650 nm) each revealed a shift in emission. Ras-Binding domain (RBD) at three concentrations (25, 37.5, 50 mu g/mL) showed that fluorescent intensity was inversely related to the concentration of protein loaded. These data support 2D FDS as a novel technique in identifying nanoparticles and their surface interactions as a quality assurance tool.
Citation: Hurst, M. N., & DeLong, R. K. (2016). Two-Dimensional Fluorescence Difference Spectroscopy to Characterize Nanoparticles and their Interactions. Scientific Reports, 6, 9. https://doi.org/10.1038/srep33287
Keywords: Ras-Binding Domain; Oxide Nanoparticles; Rna; Surface; Acid; Nanocrystals